Perioperative corticosteroid treatment impairs tumor-infiltrating dendritic cells in patients with newly diagnosed adult-type diffuse gliomas - Carenza, Claudia; Franzese, Sara; Castagna, Alessandra; Terzoli, Sara; Simonelli, Matteo; Persico, Pasquale; Bello, Lorenzo; Nibali, Marco Conti; Pessina, Federico; Kunderfranco, Paolo; Peano, Clelia; Balin, Simone; et al. (Frontiers in Immunology, 2023)
Adult-type diffuse gliomas are malignant primary brain tumors characterized by very poor prognosis. Dendritic cells (DCs) are key in priming antitumor effector functions in cancer, but their role in gliomas remains poorly understood. In this study, we characterized tumor-infiltrating DCs (TIDCs) in adult patients with newly diagnosed diffuse gliomas by using multi-parametric flow cytometry and single-cell RNA sequencing. We demonstrated that different subsets of DCs are present in the glioma microenvironment, whereas they are absent in cancer-free brain parenchyma. The largest cluster of TIDCs was characterized by a transcriptomic profile suggestive of severe functional impairment. Patients undergoing perioperative corticosteroid treatment showed a significant reduction of conventional DC1s, the DC subset with key functions in antitumor immunity. They also showed phenotypic and transcriptional evidence of a more severe functional impairment of TIDCs. Overall, the results of this study indicate that functionally impaired DCs are recruited in the glioma microenvironment. They are severely affected by dexamethasone administration, suggesting that the detrimental effects of corticosteroids on DCs may represent one of the mechanisms contributing to the already reported negative prognostic impact of steroids on glioma patient survival.